2015
DOI: 10.5194/acp-15-11701-2015
|View full text |Cite
|
Sign up to set email alerts
|

Observations of new particle formation in enhanced UV irradiance zones near cumulus clouds

Abstract: Abstract. During the CARRIBA (Cloud, Aerosol, Radiation and tuRbulence in the trade wInd regime over BArbados) campaign, the interaction between aerosol particles and cloud microphysical properties was investigated in detail, which also includes the influence of clouds on the aerosol formation. During two intensive campaigns in 2010 and 2011, helicopter-borne measurement flights were performed to investigate the thermodynamic, turbulent, microphysical, and radiative properties of trade-wind cumuli over Barbado… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
31
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(35 citation statements)
references
References 39 publications
4
31
0
Order By: Relevance
“…But based on the modeling results by Korhonen et al (2008) and Merikanto et al (2009), it can be assumed that the recently nucleated particles likely originated in the free troposphere, at least to a large extent. Alternatively, they were formed in the vicinity of trade wind cumuli, as suggested by Wehner et al (2015). According to Merikanto et al (2009), these small particles will eventually grow sufficiently so that they add to keeping up N CCN , to which they contribute roughly half of all particles in the marine aerosol (Merikanto et al, 2009).…”
Section: Discussion Of the Different Aerosol Typesmentioning
confidence: 99%
See 1 more Smart Citation
“…But based on the modeling results by Korhonen et al (2008) and Merikanto et al (2009), it can be assumed that the recently nucleated particles likely originated in the free troposphere, at least to a large extent. Alternatively, they were formed in the vicinity of trade wind cumuli, as suggested by Wehner et al (2015). According to Merikanto et al (2009), these small particles will eventually grow sufficiently so that they add to keeping up N CCN , to which they contribute roughly half of all particles in the marine aerosol (Merikanto et al, 2009).…”
Section: Discussion Of the Different Aerosol Typesmentioning
confidence: 99%
“…Growth rates observed in the tropical and subtropical MBL were reported to be roughly 1 to 6 nm h −1 in a review by Kulmala et al (2004). Based on measurements made during the CARRIBA campaigns, Wehner et al (2015) reported additional events of new particle formation with much higher growth rates of up to several nanometers per minute for particles with diameters of roughly 10 nm. These events occurred just outside of clouds, in isolated air parcels with an extent of several tens of meters.…”
Section: Particle Number Size Distributionsmentioning
confidence: 99%
“…Several explanations for this phenomenon were suggested, including enhanced UV irradiance and turbulence in the vicinity of clouds (e.g. Wehner et al 2015).…”
Section: Cloud-induced Npfmentioning
confidence: 99%
“…Given their very low vapor pressures, ELVOC are believed to be important in the earliest stages of particle formation and growth in air, while somewhat higher volatility compounds contribute more to their subsequent growth. 353,363,366,367,369,374,[380][381][382][383] However, analysis of SOA composition in some eld studies suggests that more volatile products can be found in SOA than expected based on their volatility. 384 This may be related to the particle phase and growth mechanisms.…”
Section: Soa Phasementioning
confidence: 99%